2004
DOI: 10.1038/sj.ejcn.1601995
|View full text |Cite
|
Sign up to set email alerts
|

Cereal grains, legumes and diabetes

Abstract: This review examines the evidence for the role of whole grain foods and legumes in the aetiology and management of diabetes. MedLine and SilverPlatter ('Nutrition' and 'Food Science FSTA') databases were searched to identify epidemiological and experimental studies relating to the effects of whole grain foods and legumes on indicators of carbohydrate metabolism. Epidemiological studies strongly support the suggestion that high intakes of whole grain foods protect against the development of type II diabetes mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
214
0
14

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(230 citation statements)
references
References 112 publications
2
214
0
14
Order By: Relevance
“…Previous research has suggested that increasing total fibre intake could help to reduce energy intake by decreasing hunger and/or increasing satiety and be helpful in the management of type 2 diabetes (Howarth et al, 2001;Venn and Mann, 2004). Dietary fibres have thus been proposed as key food components taken into account in the control of the current high prevalence of obesity and overweight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has suggested that increasing total fibre intake could help to reduce energy intake by decreasing hunger and/or increasing satiety and be helpful in the management of type 2 diabetes (Howarth et al, 2001;Venn and Mann, 2004). Dietary fibres have thus been proposed as key food components taken into account in the control of the current high prevalence of obesity and overweight.…”
Section: Discussionmentioning
confidence: 99%
“…(Jenkins et al, 1999;Davy and Melby, 2003;Venn and Mann, 2004). Soluble dietary fibres, such as guar gum, pectin or mucilages, reduce postprandial glycemia by delaying gastric emptying, namely through their gel-forming effect (Nuttall, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous prospective studies demonstrate that regular consumption of whole grains lowers the risk of heart disease and diabetes by 20-30%, (1,2) improves blood glucose regulation, (3) achieves better weight management over time, (4,5) and lowers the risk of certain types of cancer. (6) A critical appraisal of the body of evidence is reflected in multiple national dietary guidelines that inform the community to eat more "grain foods particularly whole grain cereals" and to reduce consumption of refined grains.…”
Section: Introductionmentioning
confidence: 99%
“…Increased consumption of whole-grain cereal foods can reduce the risk of these conditions substantially (1)(2)(3) and also correlates negatively with obesity (4). Resistant starch (RS) and nonstarch polysaccharides (NSP) are major components of dietary fiber and contribute to these benefits.…”
mentioning
confidence: 99%